2012
DOI: 10.1016/j.pscychresns.2011.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Low brain serotonin transporter binding in major depressive disorder

Abstract: We examined midbrain, medial temporal lobe, and basal ganglia serotonin transporter (SERT) distribution volume ratio (DVR) values in subjects with major depressive disorder versus healthy volunteers using a selective SERT radioligand and single photon emission computed tomography (SPECT). We hypothesized that the DVR value for SERT binding would be lower in depressed versus non-depressed subjects. [123I]-ADAM SPECT scans were acquired from 20 drug free, depressed subjects and 10 drug free, healthy volunteers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 46 publications
3
25
1
Order By: Relevance
“…In agreement with our findings, several studies have reported decreases in 5‐HTT density (Leake et al, ; Arango et al, ), 5‐HTT binding (Joensuu et al, ), and 5‐HTT immunoreactive axons (Austin et al, ) in various brain regions in depressed patients. PET studies also suggest that depression is linked to reduced 5‐HTT binding in various brain regions, which was reversed as patients recovered (Ichimiya et al, ; Parsey et al, ; Bhagwagar et al, ; Selvaraj et al, ; Newberg et al, ). Although, the connection between lower 5‐HTT function and depression is not universally observed (Staley et al, ; Savitz and Drevets, ), they raise the question of why patients with depression respond to SSRIs, which could lead to further decrease in 5‐HTT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with our findings, several studies have reported decreases in 5‐HTT density (Leake et al, ; Arango et al, ), 5‐HTT binding (Joensuu et al, ), and 5‐HTT immunoreactive axons (Austin et al, ) in various brain regions in depressed patients. PET studies also suggest that depression is linked to reduced 5‐HTT binding in various brain regions, which was reversed as patients recovered (Ichimiya et al, ; Parsey et al, ; Bhagwagar et al, ; Selvaraj et al, ; Newberg et al, ). Although, the connection between lower 5‐HTT function and depression is not universally observed (Staley et al, ; Savitz and Drevets, ), they raise the question of why patients with depression respond to SSRIs, which could lead to further decrease in 5‐HTT.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that a functional polymorphism in the human 5-HTT gene promoter (the 5-HTT gene-linked polymorphic region, 5-HTTLPR) is linked to an increased risk of developing major depression, linked to poor memory function, and linked to reduced hippocampal tissue volume (Caspi et al, 2003;O'Hara et al, 2007;Daniele et al, 2011). Moreover, neuroimaging studies show that hippocampal 5-HTT binding is altered in patients with depression (Newberg et al, 2012 ;Savitz and Drevets, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…As a secondary outcome, we found a significantly increased SERT binding in the midbrain after NAC supplementation. Because several studies have shown a relationship between reduced SERT binding and depression, it is possible there could be a mood benefit in patients with PD receiving NAC. The present study excluded patients with substantial depressive symptoms; however, future studies could be more inclusive of a broader range of symptoms, including depression.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, patients with MDD exhibit lower 5-HTT binding in the amygdala (Murrough et al, 2011), midbrain (Malison et al, 1998; Parsey et al, 2006a) medial temporal lobe, and basal ganglia (Newberg et al, 2012) compared with healthy volunteers. However, using the ligand [ 11 C]-3-amino-4-(3-dimethylamino-methylphenylsulfanyl)-benzonitrile ([ 11 C]DASB), we previously found no differences in 5-HTT binding between MDD and healthy controls (Miller et al, 2013).…”
Section: Introductionmentioning
confidence: 99%